STORAGE BEHAVIOUR OF POTATO GENOTYPES UNDER AMBIENT CONDITIONS - Bhutani, R D; Khurana, S. C (Potato Journal, 2013)
Tubers of seven potato genotypes were stored at room temperature for four years from March to May to compare their shelf life. Cv. Kufri Bahar recorded lowest weight loss due to rotting and it was closely followed by JW-160. However, physiological loss in weight was lowest in JW-160 followed by cv. Kufri Bahar. Cv. Kufri Sutlej recorded maximum weight loss due to rotting and physiological loss in weight followed by cv. Kufri Anand for weight loss due to rotting and JX-576 for physiological loss in weight. Different genotypes behaved differently over the years.